Human Rights and Religious Education: A Study with Special Reference to Islam - Kumar, Sanjeev; Harikumar (Integrated Journal for Research in Arts and Humanities, 2022)
A new set of global principles and ambitions emerged from modern human rights. Human rights are essential to any modern discussion on global ethics and justice. Critics charge human rights discourse as being ethnocentric in its focus on minorities. Human rights are intertwined with rights philosophy, which is tied to natural law in Islamic legal theory. For example, the right to life stems from the creation of mankind by God. This article discusses natural law, human beings, best interests, and religious instruction in Islamic legal philosophy. In doing so, I want to build a comprehensive Islamic viewpoint on human rights and a practical component of the issue of human rights in the Islamic world. The major purpose of the research is to investigate the creation of a contemporary human rights framework in the twentieth century. This study's research technique includes doctrinal and analytical research. The data will be acquired from numerous publications and reports by authorities. The researchers used secondary sources as well. Articles, books, journals, newspapers, and websites are examples. It is essential to recognize that different cultures may need to develop their own human rights arguments. It is also important to note religion's global effect. Ensuring universal human rights is not simple, as Islam has shown. No significant impact can be achieved by governmental or intellectual debates on human rights. I believe that most people, regardless of culture or religion, would embrace the notion if adequately educated. People's governments may have to work more to upgrade their legal systems and ensure people's rights.